A phase 1, first in human study of adenovirally transduced autologous macrophages engineered to contain an anti-HER2 chimeric antigen receptor (CAR) in subjects with HER2 overexpressing solid tumors - Bauml, Joshua; Grover, Natalie Sophia; Ronczka, Amy; Cushing, Daniel; Klichinsky, Michael; Barton, Debora; Dees, Elizabeth Claire (Journal of clinical oncology, 2021)
TPS2660Background: Adoptive T cell therapies have led to remarkable advances among patients with hematologic malignancies, but not in those with solid tumors. Macrophages are actively recruited into, and abundantly present in the solid tumor microenvironment (sTME). Tumor- associated macrophages typically evince immunosuppressive behavior, but when engineered to be proinflammatory, may be an ideal vector to administer adoptive cellular therapy in solid tumors. Furthermore, insertion of a CAR confers on the macrophages the ability to selectively recognize and phagocytose antigen overexpressing cancer cells. Additionally, CAR macrophages reprogram the sTME and present neoantigens to T cells, leading to epitope spreading and immune memory. Human Epidermal Growth Factor Receptor 2 (HER2) is overexpressed in many cancers, including but not limited to breast and gastroesophageal cancers (Table). CT-0508 is a cell product comprised of autologous monocyte-derived pro-inflammatory macrophages expressing an anti-HER2 CAR. Pre-clinical studies have shown that CT-0508 induced targeted cancer cell phagocytosis while sparing normal cells, decreased tumor burden and prolonged survival in relevant models. CT-0508 cells were safe and effective in a semi-immunocompetent mouse model of human HER2 overexpressing ovarian cancer. Methods: This is a FIH phase 1 study to evaluate safety, tolerability, cell manufacturing feasibility, trafficking, and preliminary evidence of efficacy of investigational product CT-0508 in approximately 18 subjects with locally advanced (unresectable) or metastatic solid tumors overexpressing HER2 who have failed available therapies including anti-HER2 therapies when indicated. Filgrastim will be used to mobilize autologous hematopoietic progenitor cells for monocyte collection by apheresis. The CT-0508 CAR macrophage product will be manufactured, prepared and cryopreserved from mobilized peripheral blood monocytes. The study is enrolling Group 1 subjects, who will receive CT-0508 infusion split over D1, 3 and 5. Subjects will be continually assessed for acute and cumulative toxicity. Dose limiting toxicities will be observed and addressed by a Safety Review Committee. Group 2 subjects will follow, and will receive the full CT-0508 infusion on D1. Pre and post treatment biopsies and blood samples will be collected to investigate correlates of trafficking, persistence, TME modulation, immune response and safety. Clinical trial information: NCT04660929.HER2 positivity frequencies across tumor types.TumorHER2 positive %*Bladder8-70Breast11.0-25.0Cervical2.8-3.9Colorectal1.6-5.0Esophageal12.0-14.0Cholangiocarcinoma6.3-9.0Gallbladder9.8-12.8Gastric7.0-34.0Ovarian26Salivary mucoepidermoid17.6Salivary duct30-40Testicular2.4Uterine3.0*References available upon request.